Pemanfaatan Website dan QR Code berbasis Android: Pendampingan pengembangan Desa Wisata dan Mahasiswa Peduli Stunting di Desa Rawe - Richasanty Septima S; Hendri Syahputra; Ira Zulfa (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
This community service was carried out in Rawe Village, Lut Tawar District, Central Aceh District with the aim of providing assistance for the development of tourist villages and students concerned about stunting by utilizing websites and Android-based QR Codes. The methods used are outreach, training, direct practice and evaluation/reflection. The results of the assistance show that: (1) the motivation of tourism managers to introduce the tourist area of Rawe village is formed, (2) it makes it easier for housewives to find out the causes of stunting, how to prevent it and healthy food to prevent stunting, (3) the existence of a website and QR Code makes it easier for people outside in the Rawe Village area to find out what tourism potential is in the Rawe village, (4) the final data obtained is that the percentage of children under five with poor and undernourished status is 10%